Impact of Packaging Methods on Physicochemical Properties, Flavor Profile, and Microbial Community in Low-Temperature Stored Mianning Ham - Lin Chen; Mengdie Li; Yiting Song; Wei Wang; Jiamin Zhang; Ting Bai; Ling Gan; Congxia Tang; Lili Ji (Foods, 2025)
This study aims to determine the differences in the effects of vacuum packaging and modified atmosphere packaging on the quality, flavor, and microorganisms of Mianning ham. Vacuum packaging exhibits stronger antioxidant properties (a* value), while modified atmosphere packaging inhibits microorganisms and delays the decline of Aw through CO2. A total of 249 volatile substances was determined in the ham, while 19 main flavor substances, such as 1-octanol, hexanal, 2-nonanone, and p-cresol, were identified. It was found that the packaging method significantly affected the contents of alcohols and hydrocarbons. At the phylum level, Firmicutes is the dominant bacterial community. At the genus level, in the vacuum packaging group, Tetragenococcus and Carnobacterium are the core contributing bacteria for flavor, while Staphylococcus is dominant in both packaging types and may inhibit flavor formation.